The Impact of lncRNAs and miRNAs on Apoptosis in Lung Cancer - Ghafouri-Fard, Soudeh; Aghabalazade, Amin; Shoorei, Hamed; Majidpoor, Jamal; Taheri, Mohammad; Mokhtari, Majid (Frontiers in Oncology, 2021)
Apoptosis is a coordinated cellular process that occurs in several physiological situations. Dysregulation of apoptosis has been documented in numerous pathological situations, particularly cancer. Non-coding RNAs regulate apoptosis via different mechanisms. Lung cancer is among neoplastic conditions in which the role of non-coding RNAs in the regulation of apoptosis has been investigated. Non-coding RNAs that regulate apoptosis in lung cancer have functional interactions with PI3K/Akt, PTEN, GSK-3β, NF-κB, Bcl-2, Bax, p53, mTOR and other important cancer-related pathways. Globally, over-expression of apoptosis-blocking non-coding RNAs has been associated with poor prognosis of patients, while apoptosis-promoting ones have the opposite effect. In the current paper, we describe the impact of lncRNAs and miRNAs on cell apoptosis in lung cancer.